The Differences between Learning Outcomes Using Guided Inquiry and Team Assisted Individualization (TAI) Types of Learning Models on Redox Reaction Concept Material in Grade X at SMA Negeri 2 Sigi - Mildha Y. Charin; Ratman Ratman; Vanny M. A. Tiwow (Universitas Tadulako, 2019)
This study aimed to determine the differences between students’ learning outcomes using guided inquiry-type learning model and team assisted individualization (TAI)-type learning model on redox reaction concept in grade X at SMA Negeri 2 Sigi. This study was a quasi-experiment method. The sample was class X MIA5 as an experiment class I (n = 24 students), and class X MIA1 (n = 24 students) as an experiment class II. The data analysis showed that the average score of experiment class I was 73.79, and the experimental class II was 71.45. The results of the hypothesis test with t-test two-party statistics obtained tcount = 0.86. The value was in the reception area of H0 that was between -1.68 and 1.68. The result from the statistical test showed that there was no difference between the students' learning outcomes using guided inquiry-type and team assisted individualization type learning models on redox reaction concept material in grade X at SMA Negeri 2 Sigi